Azulenium chemistry: towards new derivatives of photochromic dihydroazulenes. Issue 8 (22nd January 2016) - Petersen, Anne Ugleholdt; Jevric, Martyn; Elm, Jonas; Olsen, Stine T.; Tortzen, Christian G.; Kadziola, Anders; Mikkelsen, Kurt V.; Nielsen, Mogens Brøndsted
Abstract : The reactivity of azulenium salts, derived from photochromic dihydroazulenes (DHAs), towards a nucleophile is reported, and one regioisomer product is tautomerised into a new photochromic DHA that undergoes a ring-opening to a vinylheptafulvene (VHF). Abstract : Here we present the preparation of a selection of azulenium ions by hydride abstraction from photochromic 1, 8a-dihydroazulenes (1, 8a-DHAs) incorporating two cyano groups at C-1. The reactivity of the electrophilic tropylium ring of these molecules towards lithium triisopropylsilylacetylide was investigated. The position of attack by the nucleophile depended on the substitution pattern of the azulenium cation but was in general found to occur preferentially at positions C-4, C-5, and C-6, and to a minor extent at positions C-7 and C-8. The outcome was a mixture of non-photochromic, regioisomeric DHAs. One of these compounds containing the ethynyl substituent at position C-4 was partly tautomerized to the photochromic 1, 8a-dihydroazulene, which was isolated and its switching properties were investigated by UV-Vis absorption spectroscopy. Upon irradiation, it undergoes a ring-opening reaction to form a vinylheptafulvene (VHF), which in turn returns to the original DHA. The half-life of this reaction was significantly smaller than for a derivative with the alkynyl substituent placed at C-7. This fast switching behavior was according to the calculations explained by an enhancement in the stability of the reactive s- cis conformer of the VHF relative to the, still more stable, s- trans conformer, and by a smaller activation energy for this s- cis conformer to undergo ring-closure.